SURVEY OF WINDOWPANE OYSTER (PLACENTA PLACENTA) RESOURCES IN THE KAKINADA BAY - Murty, V Sriramachandra; Narasimham, K A; Venugopalam, W (Indian Journal of Fisheries, 2011)
An estimated population of live window-pane oyster of 8,945.3 tonnes and 43,347.6 tonnes of shells of dead oyster is ;n the Kakinada Bay, spread out in an area of 132 sq. km. The live oyster is confinsd to western and southern sides of the Bay which are known to be reh lively more productive. The shells of dead oyster are spread all over the Bay with very large concentration on the eastern side. The fishermen remove window-pane oyster available on the southern and western sides during January-May and the catches are utilised mainly for manufacture of lime. It is suggested that extension of fishing season along vwith extension of fishing ground to the eastern and central portions of the Bay will result in greater yield of this resource. There is considerable scope in utilisation of this resource by extracting pearls formed in them and also flesh being used as an item of food.